Muzyka i muzycy w dokumentach Kanoników Regularnych Laterańskich (1781–1861) - Grajewski, Czesław (Studia Pastoralne, 2026)
The author of the article has analyzed protocols (files) of the general chapters as well as protocols from visitations to monasteries of the Canons Regular of the Lateran (CRL) in the Kraków Province between 1781 and 1861. The protocols are currently in the archives of the Pauline Fathers in Częstochowa (ms. 253 and ms. 254), where they were placed after the dissolution of monasteries ordered by the Russian authorities following the January Uprising. This article centers on topics related to music which are present in the documents mentioned above. The author identified the following two topics: A) performance of liturgical music; B) people involved in the music culture: Gregorian chant teachers, organists as well as anonymous figures. Several dozen notes in both manuscripts demonstrate concern of the Canons Regular for the quality of music in their monasteries.